E- migrant: technological, geographical and social spaces. New actors and spaces for political participation? - Mauricio Nihil Olivera (Comunicação e Sociedade, 2015)
This article is based on the results provided by the research project named “A study of recent migratory movement from Spain to Uruguay. New technological, geographical and social spaces for citizen vincluation” (Olivera et al., 2014) and, by using the concept of “e-migrant”, it analyses if the introduction of ICTs enables the renewal of the traditional forms of political participation and public decision-making. Having the concept of e-migration as a starting point, the article aims at identifying what are the forms and the type of communication networks used by the new Spanish migrants as well as the way they connect and communicate (politically, socially and culturally) in Uruguay. It also aims at problematizing these issues under the light of the Social Sciences theories, following the critical investigative line of research about the “Information Society”. The authors argue that the ways new Spanish migrants connect to each other in Uruguay are dialectic relationships and are also a result of a social process that depends on the decisions and on the significances given by individuals. These decisions and subjectivities are not determined solely by the structures that are inherent to their condition as migrants, neither are they totally contingent to this condition; they move in a space of possible configurations in order to be re-signified in concrete situations.